Study and Analysis of Graduates' Employment, Adaptation, and Professional Growth (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article presents a comprehensive study on the employment, adaptation, and professional development of university graduates. It analyzes key factors influencing job placement, challenges faced during the transition from academia to the workforce, and the long-term career progression of graduates. Special attention is given to the role of higher education institutions in preparing students for professional life and supporting their early career development. The article explains the objective limitations of the ability of higher education to respond promptly to dynamic changes in the labor market, as well as the aggravation of the problem of employment of university graduates in the current socio-economic situation in the country, caused by changes in the employment structure and limited interaction between emerging employers and higher education.